Affecting factors and recent improvements of the photochemical reflectance index (pri) for remotely sensing foliar, canopy and ecosystemic radiation-use efficiencies - Zhang, Chao (2016)
Accurately assessing terrestrial gross primary productivity (GPP) is crucial for characterizing the climate-carbon cycle. Remotely sensing the photochemical reflectance index (PRI) across vegetation functional types and spatiotemporal scales has received increasing attention for monitoring photosynthetic performance and simulating GPP over the last two decades. The factors confounding PRI variation, especially on long timescales, however, require the improvement of PRI understanding to generalize its use for estimating carbon uptake. In this review, we summarize the most recent publications that have reported the factors affecting PRI variation across diurnal and seasonal scales at foliar, canopy and ecosystemic levels; synthesize the reported correlations between PRI and ecophysiological variables, particularly with radiation-use efficiency (RUE) and net carbon uptake; and analyze the improvements in PRI implementation. Long-term variation of PRI could be attributed to changes in the size of constitutive pigment pools instead of xanthophyll de-epoxidation, which controls the facultative short-term changes in PRI. Structural changes at canopy and ecosystemic levels can also affect PRI variation. Our review of the scientific literature on PRI suggests that PRI is a good proxy of photosynthetic efficiency at different spatial and temporal scales. Correcting PRI by decreasing the influence of physical or physiological factors on PRI greatly strengthens the relationships between PRI and RUE and GPP. Combining PRI with solar-induced fluorescence (SIF) and optical indices for green biomass offers additional prospects.